Analisis Peran Dewan Pengawas Syariah dalam Menjaga Kepatuhan Syariah pada Bank Syariah Indonesia - Chabi Baturohmah; Dian Fadilah; Fikri Rizki Utama (Indonesia Economic Journal, 2026)
The development of Islamic banking in Indonesia has shown a significant upward trend, driven by increasing public awareness of sharia-based financial systems. The establishment of Bank Syariah Indonesia as a result of the merger of state-owned Islamic banks marks an important milestone in strengthening the national Islamic banking industry. However, such growth must be balanced with optimal sharia compliance to maintain public trust. In this context, the Dewan Pengawas Syariah (Sharia Supervisory Board) plays a strategic role in ensuring that all banking operations comply with Islamic principles. This study aims to analyze the role of the Sharia Supervisory Board in maintaining sharia compliance at Bank Syariah Indonesia. The research employs a descriptive qualitative approach through literature review by examining relevant academic sources. The results indicate that the Sharia Supervisory Board plays a crucial role in operational supervision, product validation, sharia auditing, and the implementation of good corporate governance principles. Additionally, the board contributes to enhancing public trust in Islamic banking. Nevertheless, its effectiveness still faces several challenges, including limited human resource competencies and the complexity of modern financial products. Therefore, strengthening the capacity and adaptability of the Sharia Supervisory Board is necessary to ensure sustainable sharia compliance.